Desain Tata Ruang Perpustakaan Daerah Kota Padang Panjang Berbasis Teknologi di Era 5.0 - Afrina, Cut; Aninsa, Annisa; Zamharira, Assyifa Aliya Zamharira Aliya; Meta, Nadia; Lian, Putri (Jurnal Tadwin, 2022)
This study aims to find out about the regional spatial design in the city of Padang Panjang which is based on technology in the 5.0 era. As well as knowing the meaning and function of the Padang Panjang city regional library. The results of this study indicate the spatial design of the Padang Panjang regional library which takes an innovative approach to the development of technology facilities and infrastructure with the aim of developing literacy and illiteracy rates in society. In this 5.0 era, the layout design of the library continues to require development, both in upgrading the layout of the library as well as in adding library technology facilities. The role of libraries in the 5.0 era which continues to undergo transformation according to the vision and mission of digital libraries to remain a permanent information service provider that an existence among library users.